A conceptual model identifying apartment owners' attitude formation towards solar photovoltaic (PV) adoption. Issue 3 (15th March 2021) - Charters, Ben; Heffernan, Troy
Abstract : Purpose: This paper addresses the current lack of solar photovoltaic (PV) adoption by Australian apartment dwellers by proposing a conceptual model that identifies and integrates the factors influencing owners' attitudes towards PV adoption. Design/methodology/approach: The conceptual model, which this paper terms the apartment-based solar adoption (ASA) model, is developed by applying motivation–opportunity–ability (MOA) theory to relevant findings in property development, green energy and strata governance literature. Findings: The ASA model demonstrates the process by which an apartment-owning consumer may progress from considering solar PV adoption to recommending the action to their strata property's Owners' Committee (OC). It incorporates three motivational drivers (pragmatic considerations, perceived values and perceived social norms), three conditional mediators (location accessibility, resource availability and decision-making conditions) and three requirements from the consumer (actual and perceived knowledge, the ability to participate in decision-making and social connections and status). Research limitations/implications: This article contributes originality to research on two counts. Firstly, it provides a conceptual framework of specific relevance to issues concerning solar PV adoption, and secondly, it offers a systematic means for research into strata governance decision-making. Further research is required to develop the means with which to utilise the model prescriptively and measure longitudinal effects, such as ongoing trends in apartment owners' motivations. Further research is also recommended into how the ASA model may be utilised to identify generalisable consumer typologies among apartment owners. Practical implications: The ASA model may assist building maintenance providers in developing and marketing solar PV services tailored to apartment residents' requirements and enhance strata managers' ability to inform and guide apartment owners. In turn, property developers would be able to review apartment-based solar projects, measure their increased value and decreased energy costs and incorporate this information when planning future developments. Social implications: The ASA model may provide a template for apartment owners and owners' corporations considering solar PV for their property. Public policymakers could also refer to the model to incentivise apartment-based solar PV adoption, whether through designing local information campaigns, developing financial incentives or mitigating identified regulatory barriers. By facilitating solar PV adoption in Australian apartment housing, the model may ensure sustainable post-carbon energy consumption for Australia's housing stock and act as an example for high-density housing development internationally. Originality/value: The ASA model addresses the many drivers and barriers known to affect solar PV adoption by apartment owners, presenting a framework on which to arrange these factors and outline their causal relationships. This framework may inform strata properties' future solar PV adoption initiatives by incorporating their specific physical characteristics, stakeholder dynamics and institutional structure. It also consolidates and provides generalisability to the concepts established in current literature.